Biblioteca – spațiu de sprijin și creativitate pentru copii și adolescenți. Un model de colaborare dintre Biblioteca Municipală „B.P. Hasdeu” și Centrul comunitar WeWorld - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2026)
Between January and July 2025, the B.P. Hasdeu Municipal Library implemented a comprehensive program of activities for children and adolescents, carried out in partnership with the international organization WeWorld. Through this project, five spaces within the Central Library were renovated and transformed into areas dedicated to psychosocial, speech therapy, educational, and recreational activities. The project included creative workshops, robotics sessions, individual and group counseling, youth camps, and participation in the summer program “Summer Challenge”. This initiative demonstrated the significant impact libraries can have in supporting the emotional and social development of young people, while contributing to community cohesion.